Mortality and serum insulin-like growth factor (IGF)-I and IGF binding protein 3 concentrations - Friedrich, Nele; Haring, Robin; Nauck, Matthias; Lüdemann, Jan; Rosskopf, Dieter; Spilcke-Liss, Elisabeth; Felix, Stephan B; Dörr, Marcus; Brabant, Georg; Völzke, Henry; Wallaschofski, Henri (The journal of clinical endocrinology and metabolism, 2009)
Previous studies provided conflicting results regarding the association of serum IGF-I or IGF-binding protein-3 (IGFBP-3) and mortality. The aim of this study was to assess the relation of IGF-I and IGFBP-3 levels with mortality from all causes, cardiovascular disease (CVD), and cancer in a prospective population-based study. From the Study of Health in Pomerania (SHIP) 1988 men and 2069 women aged 20-79 yr were followed up on average 8.5 yr. Causes of deaths were coded according to the International Classification of Diseases, 10th revision. Serum IGF-I and IGFBP-3 levels were determined by chemiluminescence immunoassays and categorized into three groups (low, normal, high) according to the sex- and age-specific 10th and 90th percentiles. Adjusted analyses revealed that men with low but not high IGF-I levels had an almost 2-fold higher risk of all-cause mortality [hazard ratio (HR) 1.92 (95% confidence interval [CI] 1.35; 2.73)], CVD mortality [HR 1.92 (95% CI 1.00; 3.71)], and cancer mortality [HR 1.85 (95% CI 1.00; 3.45)] compared with men with normal IGF-I levels. In women, no association between IGF-I and mortality was found. Moreover, low IGFBP-3 levels were associated with higher all-cause mortality in men [HR 1.87 (95% CI 1.31; 2.64)] and women [HR 1.63 (95% CI 0.96; 2.76)]. The present study found inverse associations between IGF-I or IGFBP-3 levels and mortality from all causes, CVD, or cancer in men and between IGFBP-3 and all-cause mortality in women.